Parent-adolescent communication and self-reported sexual health risk behaviour among adolescent girls: a cross-sectional study - Ririn Harini; Elsa Risma Hidayah; Yuni Sufyanti Arief; Mira Triharini (Pediomaternal Nursing Journal, 2026)
Introduction: Parent–adolescent communication correlates with reduced adolescent sexual health risk, but Indonesian cultural taboos around sexuality complicate parent-child dialogue. Objective: To examine unadjusted associations between five communication dimensions (openness, support, positivity, empathy, equality) and self-reported sexual health risk behaviour among adolescent girls in East Java, Indonesia. Methods: This cross-sectional study (STROBE-reported) surveyed 159 girls aged 13–15 at Public Junior High School Lamongan (July 26–27, 2022), using validated scales for communication quality (40 items, α = .89) and risk behaviour (15 items, α = .86). Communication scores were analysed continuously via Spearman correlation and dichotomised at the median for cross-tabulation. Given only 13 at-risk participants, sparse tables were assessed with Fisher's exact tests, reporting crude odds ratios (ORs) with 95% CIs. Results: Most participants (91.8%) reported no risk behaviour. Risk prevalence among those with poor communication ranged from 15.0% (support) to 69.2% (equality), versus 1.3–3.6% among those with good communication. Good communication rates varied by dimension: equality (91.8%), positivity (88.1%), empathy (86.8%), openness (79.9%), support (49.7%). All five dimensions were negatively associated with risk behaviour (P-value = −.268 to −.456; P-value = .001 for support, P-value < .001 for others). Crude ORs ranged from 12.0 (95% CI 3.4–42.4, openness) to 79.9 (95% CI 17.1–373.0, equality), though wide confidence intervals reflect the small at-risk sample. Conclusion: Better parent–adolescent communication was associated with lower risk-behaviour prevalence, but the cross sectional, unadjusted, single-school design with sparse outcomes precludes causal claims. Findings may inform sexual health promotion strategies, interpreted cautiously given limited generalisability. Keywords: adolescent girls; family communication; parent–adolescent communication; sexual health risk behaviour